2000
DOI: 10.1037/0022-3514.79.5.701
|View full text |Cite
|
Sign up to set email alerts
|

The role of transportation in the persuasiveness of public narratives.

Abstract: Transportation was proposed as a mechanism whereby narratives can affect beliefs. Defined as absorption into a story, transportation entails imagery, affect, and attentional focus. A transportation scale was developed and validated. Experiment 1 (N = 97) demonstrated that extent of transportation augmented story-consistent beliefs and favorable evaluations of protagonists. Experiment 2 (N = 69) showed that highly transported readers found fewer false notes in a story than less-transported readers. Experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

104
3,648
11
98

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 3,024 publications
(3,861 citation statements)
references
References 25 publications
104
3,648
11
98
Order By: Relevance
“…Empirical research has repeatedly demonstrated the power of narratives to persuade recipients, even if the stories were introduced as fictional (e.g., Appel & Mara, 2013; Green & Brock, 2000; Prentice, Gerrig, & Bailis, 1997). Narratives often engage the recipient and transport him or her into the world of the story ( transportation ; Gerrig, 1993; Green & Brock, 2000). This state of transportation, rather than the elaboration of arguments (cf., Petty & Cacioppo, 1986), is considered to play a key role in narrative persuasion.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Empirical research has repeatedly demonstrated the power of narratives to persuade recipients, even if the stories were introduced as fictional (e.g., Appel & Mara, 2013; Green & Brock, 2000; Prentice, Gerrig, & Bailis, 1997). Narratives often engage the recipient and transport him or her into the world of the story ( transportation ; Gerrig, 1993; Green & Brock, 2000). This state of transportation, rather than the elaboration of arguments (cf., Petty & Cacioppo, 1986), is considered to play a key role in narrative persuasion.…”
Section: Introductionmentioning
confidence: 99%
“…Stories entail the actions and experiences of one or more protagonists and a plot line with certain schematic elements (e.g., setting, event, attempt, reaction, and consequence; Rumelhart, 1975). In recent years, empirical research has demonstrated that fictional as well as nonfictional narratives can have a pervasive impact on attitudes and beliefs about real-world issues (narrative persuasion; e.g., Green & Brock, 2000; Prentice et al, 1997), on knowledge and memory (Fazio & Marsh, 2008; Marsh, Meade, & Roediger, 2003), and on social abilities and personality (Fong, Mullin, & Mar, 2013; Mar & Oatley, 2008). In some of these studies the stories as a whole or their main narrative arc suggested a particular stance toward a topic (e.g., a story about a psychiatric patient who murdered a child led recipients to have more negative beliefs about the group of psychiatric patients; Green & Brock, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations